PENGEMBANGAN INDIKATOR 4C’S YANG SELARAS DENGAN KURIKULUM 2013 PADA MATA PELAJARAN MATEMATIKA SMA/MA KELAS XI SEMESTER 1 - Anggraeni, Anggraeni; Sunardi, Sunardi; Kurniati, Dian (Kadikma, 2017)
Abstract. This research will be conducted to describe process and result of development of 4C's indicators which appropriate for curriculum 2013 on mathematics subject in the first semester of senior high school grade XI. Development process which used in this research is Plomp Development model which consist of four stages, they are preliminary implementation phase, design phase, realization/construction phase, and test, evaluation, and revision. The result of the development of indicators amounted to 94 indicators 4C's which consist of five materials and 14 KD at mathematics lesson. The result of assessment by five validators are then calculated and analyzed. The 4C's indicators is categorized well, because the total average calculation result for each aspect is 3.77. It is that the resulting product is valid. The productcan be valid if the total average calculation result for each aspect is more than equal to 3.25. Keywords: 4C's Indicators, Curriculum 2013, Plomp's Development Model